2022
DOI: 10.1002/er.8562
|View full text |Cite
|
Sign up to set email alerts
|

Reversible hydrogen storage capacity of Li and Sc doped novel C 8 N 8 cage: Insights from density functional theory

Abstract: Summary In this work, we designed and addressed the hydrogen storage capacities of Li and Sc doped novel C8N8 cages using dispersion corrected density functional theory (DFT‐D3). The stabilities of C8N8Li2 and C8N8Sc2 cages were confirmed by chemical hardness, HOMO‐LUMO gaps, and molecular dynamic simulations. Both C8N8Li2 and C8N8Sc2 could adsorb 5H2 molecules with an average hydrogen adsorption energy of 0.187 and 0.291 eV/H2, keeping the original structure intact. The H2 molecules interacted with the Li/Sc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…This is essential for evaluating the practicality of a material for hydrogen storage applications, especially in the context of clean energy technologies. The gravimetric density can be expressed using eq . , C wt 0.25em % = [ p M normalH ( M com + p M normalH ) ] × 100 % …”
Section: Resultsmentioning
confidence: 99%
“…This is essential for evaluating the practicality of a material for hydrogen storage applications, especially in the context of clean energy technologies. The gravimetric density can be expressed using eq . , C wt 0.25em % = [ p M normalH ( M com + p M normalH ) ] × 100 % …”
Section: Resultsmentioning
confidence: 99%
“…33 Chakraborty et al studied the yttrium doped single-walled carbon nanotube and revealed 6.1 wt % of storage capacity with 100% desorption of H 2 at 612 K. 34 The same group investigated Ti-doped Ѱ-Graphene and predicted the H 2 storage capacity of up to 13.14 wt% with an adsorption energy of 0.30 eV and average desorption temperature of 387 K. 35 The Yttrium atom attached on graphyne surface as a hydrogen storage candidate was explored by Gangan et al and they reported the system can adsorb up to a maximum of 9H 2 , (10 wt%) with an adsorption energy of $0.3 eV/H 2 and an average desorption temperature of around 400 K. 36 Sahoo et al reported storage of H 2 on Li and Sc doped C 8 N 8 cage via Niu-Rao-Jena and Kubas interaction and estimated a desorption temperature of 286 K and 456 K, respectively. 37 The Li and Na doped on C 24 fullerene could adsorb H 2 molecules, with average hydrogen binding energies of 0.198 eV/H 2 and 0.164 eV/H 2 and led to gravimetric uptake capacity of up to 12.7 wt% and 10 wt%, respectively. 38 Recently, we have investigated the H 2 storage on C 20 fullerene doped with alkali metals and found the molecular hydrogen are physisorbed on host material via charge polarization mechanism with desorption temperature of 182-191 K. 39 Each Li and Na atom doped with C 20 could uptake up to 5H 2 molecules, lead to H 2 gravimetric storage capacity of 13.08 and 10.82 wt%, respectively, and the H 2 binding energies found between 0.12 eV and 0.13 eV/H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The Yttrium atom attached on graphyne surface as a hydrogen storage candidate was explored by Gangan et al and they reported the system can adsorb up to a maximum of 9H 2 , (10 wt%) with an adsorption energy of ~0.3 eV/H 2 and an average desorption temperature of around 400 K 36 . Sahoo et al reported storage of H 2 on Li and Sc doped C 8 N 8 cage via Niu–Rao–Jena and Kubas interaction and estimated a desorption temperature of 286 K and 456 K, respectively 37 . The Li and Na doped on C 24 fullerene could adsorb H 2 molecules, with average hydrogen binding energies of 0.198 eV/H 2 and 0.164 eV/H 2 and led to gravimetric uptake capacity of up to 12.7 wt% and 10 wt%, respectively 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In the beginning, carbon nanostructures gained more popularity for the investigation of hydrogen storage media due to their lightweight and the presence of a large surface-to-volume ratio. However, due to the weaker Van der Waal interaction energy between the adsorbed H 2 molecules and the carbon surface, pure carbon nanostructures were found to be unsuitable for optimum H 2 adsorption. , Various techniques, such as substituting heteroatoms like B, N, and Si and encapsulating suitable foreign atoms followed by metal functionalization over these pure nanostructures, have been reported to tune the overall electronic properties of the host system, making them more favorable for H 2 adsorption with a stronger binding energy than the pristine nanostructures. For instance, the surfaces of the Si doped single-walled carbon nanotubes (SWNT) and graphene adsorb more H 2 molecules with higher binding energy than their pristine counterparts .…”
Section: Introductionmentioning
confidence: 99%